IMPLEMENTASI FUNGSI KELEMBAGAAN BADAN PERMUSYAWARATAN DESA DI DESA LASIROKU KECAMATAN IWOIMENDAA KABUPATEN KOLAKA - Irvan Abadi, A Muh; Muhammadiah, Muhammadiah; Adys, Abdul Kadir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of the study was to determine the function of the Institutional Protector of the Village Consultative Body in Lasiroku Village, Iwoimendaa District, Kolaka Regency and to determine the Institutional Supervision Function of the Village Consultative Body in Lasiroku Village, Iwoimendaa District, Kolaka Regency. This type of research uses a qualitative descriptive type of research. Data analysis techniques using data reduction steps, data presentation and the final stage. The results showed that 1) the function of accommodating and channeling the aspirations of the village community was to accommodate and channel the aspirations of the community, in carrying out its function the BPD in Lasiroku Village, Iwoimendaa District had not been carried out properly, 2) The supervisory function to supervise villages in Lasiroku Village, Iwoimendaa District was quite implemented. well. The BPD of Lasiroku Village, Iwoimendaa District is always active in questioning matters relating to the administration of the Village Government related to the planning of Village activities, implementation of activities and reporting of Village Government activities.Keywords: Implementation, Institutional Function